2010
DOI: 10.1200/jco.2009.26.6114
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy Compared With Surgery Alone for Locally Advanced Cancer of the Stomach and Cardia: European Organisation for Research and Treatment of Cancer Randomized Trial 40954

Abstract: This trial showed a significantly increased R0 resection rate but failed to demonstrate a survival benefit. Possible explanations are low statistical power, a high rate of proximal gastric cancer including AEG and/or a better outcome than expected after radical surgery alone due to the high quality of surgery with resections of regional lymph nodes outside the perigastic area (celiac trunc, hepatic ligament, lymph node at a. lienalis; D2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
479
2
24

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 620 publications
(526 citation statements)
references
References 17 publications
21
479
2
24
Order By: Relevance
“…The European group has reported recently that R0 surgery increased but did not affect overall survival. 28 Kochi and his colleagues have reported the efficacy of neoadjuvant S-1þCDDP. 29 Before any conclusive results come out by the well-organized studies, we should be careful in adopting neoadjuvant chemotherapy in the clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The European group has reported recently that R0 surgery increased but did not affect overall survival. 28 Kochi and his colleagues have reported the efficacy of neoadjuvant S-1þCDDP. 29 Before any conclusive results come out by the well-organized studies, we should be careful in adopting neoadjuvant chemotherapy in the clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…In this trial, three ECF cycles (5-fluorouracil , cisplatin, and epirubicin) were given before and after surgery, and there was a significant improvement in OS of 7.4 and 12.5 % after 4 and 5 years compared with surgery alone, respectively. Data on neoadjuvant chemotherapy has been available from at least five randomized trials that included patients with lower esophageal adenocarcinoma [5,[35][36][37][38][39].…”
Section: Surgerymentioning
confidence: 99%
“…Several metaanalyses have demonstrated a statistically significant benefit for neoadjuvant chemotherapy [40][41][42]. The EORTC 40954 trial, which primarily included patients with AEG junction, contributed to the evidence for neoadjuvant chemotherapy [37]. In this trial, cisplatin/5-FU as a PLF regimen was used only preoperatively.…”
Section: Surgerymentioning
confidence: 99%
“…40 In recent years, there have been advances in the surgical approach with combining gastrectomy with limited lymphadenectomy in a Western setting 41 and D2 lymphadenectomy in an Asian setting 42 and the use of preoperative chemotherapy to increase the R0 resection rate. 43 It has also been shown that combination chemotherapy significantly improves survival compared to single agent 5-fluorouracil, however, at the expensive of increased toxicity. 44 Most recently, the ToGA study as previously alluded to, demonstrated the efficacy of combining trastuzumab with chemotherapy.…”
Section: Presence Of Metastases (M)mentioning
confidence: 99%